The Private Shareholder and the Corporate Report (Book). - Burns, Thomas J.; Ferris, Kenneth R. (The Accounting Review, 1978)
Reviews the book "The Private Shareholder and the Corporate Report," by T.A. Lee and D.P. Tweedie.